Elementary School Students’ Reflections On Chess Learning Difficulties - Gharakhanyan, Lusine; Sargsyan, Vahan (Զանգակ հրատ.)
According to the studies, reflection is a significant aspect of educational activities. Chess fosters constant analysis and reflection on different positions. It has also been revealed that students’ reflective style is more prevalent during chess lessons. Current research aims to reveal chess learning difficulties and developmental trends based on elementary school students' reflective judgments. We combined qualitative and quantitative approaches in our study. A questionnaire was designed to evaluate the reflexive environment and the students’ reflective skills based on the principles of reflective activity theory. The questionnaire included questions about likes and dislikes in chess class, self-sufficiency, success, challenges, need for help, praise received, and teacher support. An open-ended section was added for additional comments. Conducted in 2024, the study involved 107 students. Responses were scored using reflective activity theory, with points for overcoming difficulties, constructive feedback, independence, and engagement. Our research analysis reveals that chess teaching is seen positively, and the difficulty with subject complexity was common among students, potentially affecting learning effectiveness, especially with limited class time. The authors underline the necessity of future research by involving teachers in developing student reflection to share experiences and solutions for typical cases.
Keywords: Education